Facile synthesis of triazine-based microporous organic network for high-efficient adsorption of flumequine and nadifloxacin: A comprehensive study on adsorption mechanisms and practical application potentials. (February 2023) - Zhao, Zhe; Lin, Shumin; Yu, Zhendong; Su, Ming; Liang, Bolong; Liang, Shu-Xuan; Ju, Xue-Hai
Abstract: Flumequine (FLU) and nadifloxacin (NAD), as emerging contaminants, have received extensive attention recently. In this study, a triazine-based microporous organic network (TMON) was synthetized and developed as an excellent adsorbent for FLU and NAD. The adsorption behavior and influence factors were investigated in both single and binary systems. Insight into the adsorption mechanisms were conducted through experiments, models, and computational studies, from macro and micro perspectives including functional groups, adsorption sites, adsorption energy and frontier molecular orbital. The results showed that the maximum adsorption capacities of TMON for FLU and NAD are 325.27 and 302.28 mg/g under 30 °C higher than records reported before. TMON exhibits the better adaptability and anti-interference ability for influence factors, leading to the preferable application effect in kinds of real water samples. TMON also shows the application potentials for the adsorption of other quinolone antibiotics and CO2 capture. Hydrogen-bonding interaction played the most critical role compared to π-π stacking effect, π-π electron-donor-acceptor interaction, CH-π interaction, and hydrophobic interaction during the adsorption. TMON could be regarded as a promising environmental adsorbent for its large surface area, stable physical and chemical properties, excellent recyclability, and wide range of applications. Graphical abstract: Image 1 Highlights: The adsorption performance were enhanced by inducing triazine ring to MON. The maximum adsorption capacity for FLU and NAD was 325.27 and 302.28 mg/g. TMON possessed the capture potential for CO2 . Hydrogen-bonding interaction dominate the excellent adsorption. HPMTBS and DFT calculation was employed to reveal the adsorption mechanisms.